Method for selectively extracting rubidium from lithium ore tailings in short process
By using calcium chloride and oxalic acid as additives for chlorination and water-soaking in lithium ore tailings sand, combined with the homemade rubidium extracting composite material for selective extraction of rubidium, the problems of large energy consumption and many impurities in the prior art are solved, and efficient directional recycling and utilization of rubidium resources are achieved.
Patent Information
- Application Number
- CN202411991354.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing rubidium extraction method in lithium ore tailings sand has insufficient performance under a stronger chemical environment, high energy consumption and many impurities, and it is difficult to achieve directional extraction and utilization of rubidium resources.
The metal elements in the tailing sand are released by mixing calcium chloride and oxalic acid as additives through chlorination and calcination combined with water immersion, and the rubidium elements in the rubidium enrichment liquid are selectively extracted using homemade rubidium extract composite material to separate the remaining impurity elements.
Release of rubidium elements in a short time under relatively low temperature environments improves the resource utilization effect of rubidium, reduces energy consumption and environmental pollution, reduces the cost of rubidium extraction, and improves economic benefits.
Smart Images

Figure CN119913365A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of comprehensive utilization of mineral wastes, and in particular to a method for selectively extracting rubidium in a short process in lithium ore tailings. Background Art
[0002] There are three main processes for extracting lithium from lepidolite: acid method, alkali method, salt method, pressure cooking method, etc. In the process of producing these lithium salts, a large amount of lithium tailings will be generated as industrial waste. It is estimated that the output of 1 ton of lithium carbonate salt is 8 to 10 tons of lithium tailings.
[0003] Research on the comprehensive utilization of lithium tailings is mainly focused on direct application in building materials such as concrete, cement mortar and cement, as well as the preparation of ceramics, building ceramsite, molecular sieves, etc. The technology is relatively backward, and the cost of processing one ton of lithium tailings is about 200 yuan, which is relatively high, making it difficult to reprocess lithium tailings in actual factory production. However, in addition to the extraction of valuable metal lithium, high-value metal rubidium can be extracted from lithium ore to realize the resource utilization of solid waste.
[0004] Rubidium is a soft, active, rare metal with unique photoelectric properties. It is also one of the most valuable rare alkali metals and is widely used in traditional fields such as atomic clocks, photovoltaic cells, special glass, biochemistry, and medicine. In particular, with the rapid development of rubidium in emerging application fields such as magnetohydrodynamic power generation, thermal ion conversion power generation, and ion propulsion engines, the demand for rubidium has also increased significantly year by year.
[0005] In the past, the method of extracting rubidium from lithium mica was mainly divided into the following steps: crushing the original ore sand, adding additives to the crushed ore sand for high-temperature roasting, then directly leaching the roasted product at a certain speed, then thoroughly washing the leached ore sand and liquid with deionized water to achieve solid-liquid separation, and extracting rubidium in the form of rubidium salt with the washed leaching liquid. However, each step is carried out under a strong chemical environment, resulting in high energy consumption. At the same time, there are a large number of other metal impurities besides rubidium in the leaching liquid, making it difficult to achieve directional extraction and utilization of rubidium resources. For example, in the method provided by CN114107674A, microwave heating needs to be roasted at 1000-1600°C. In the method of CN115725856A, ion exchange method is used to extract rubidium. Although high-temperature roasting is not required, the leaching time requires 24 hours. Although the method of CN113337734A can extract rubidium at a reduced temperature, other metal elements are mixed in the rubidium-enriched solution and effective separation cannot be achieved. Summary of the invention
[0006] In view of the shortcomings of the above-mentioned existing rubidium extraction methods, such as the need to carry out the reaction in a strong chemical environment, high energy consumption, and many impurities, the present invention provides a method for selectively extracting rubidium in lithium ore tailings in a short process, which adopts a mixture of calcium chloride and oxalic acid as an additive, releases the metal elements in the tailings by chlorination roasting combined with leaching, combines the selective extraction of rubidium elements in rubidium-enriched solution with a homemade rubidium extraction composite material, separates the remaining impurity elements, and improves the purity of rubidium-containing substances, thereby providing a new idea for the directional recovery and utilization of rubidium resources in lithium ore tailings.
[0007] The present invention adopts the following technical solutions:
[0008] A method for selectively extracting rubidium from lithium ore tailings in a short process, comprising the following steps:
[0009] S1. Grinding the lithium ore tailings to obtain lithium ore tailings powder;
[0010] S2. The lithium ore tailings powder obtained in step S1 and the composite additive are fully mixed to obtain a raw material raw material, wherein the composite additive is a mixture of calcium chloride and oxalic acid;
[0011] S3. The raw material obtained in step S2 is roasted to obtain a roasted material;
[0012] S4. The calcined slag obtained in step S3 is cooled to room temperature and then leached in water, and the leaching liquid is separated by solid-liquid separation to obtain a rubidium-enriched solution (leaching solution) and leaching slag;
[0013] S5. Selecting a rubidium-extracted composite material and mixing it with the rubidium-enriched solution obtained in step S4 to obtain a mixed solution, wherein the rubidium-extracted composite material is a metal organic framework material (MOFs);
[0014] S6. The mixed liquid obtained in S5 is subjected to solid-liquid separation to separate rubidium-enriched material; the rubidium-enriched material is placed in a KCl solution, heated for desorption treatment, and after solid-liquid separation, a rubidium-enriched pure liquid and a regenerated rubidium-extracted composite material are obtained.
[0015] Furthermore, in step S1, the particle size of the lithium ore tailings powder is controlled to be greater than 98% in the range of 0 to 100 μm, and more preferably, the particle size of the lithium ore tailings powder is controlled to be greater than 90% in the range of 0 to 75 μm.
[0016] Furthermore, in step S2, the mass ratio of calcium chloride to oxalic acid is 0.3-0.6:0.5, preferably 0.4-0.5:0.5.
[0017] Furthermore, in step S3, the calcination temperature is 600-900° C., and the calcination time is 0.5-3 h.
[0018] Furthermore, in step S4, the water immersion temperature is 25 to 90° C., and the time is 2 to 120 minutes.
[0019] Furthermore, in step S4, the roasting material is in powder form and does not need to be further ground, and the mass ratio of the roasting material to water is 1:2-10.
[0020] Furthermore, in step S5, the stirring speed is 100-950 r / min, the mixing temperature is 20-80° C., and the mixing time is 2 min-2 h.
[0021] Furthermore, in step S5, the metal organic framework material (MOFs) is prepared by a conventional method in the prior art using at least one of potassium ferrocyanide trihydrate, cobalt nitrate hexahydrate, p-phenylene carboxylic acid, DMF, acetic acid and zirconium oxychloride octahydrate as a raw material as needed.
[0022] Furthermore, in step S5, the mass ratio of the rubidium-extracted composite material to the rubidium-enriched solution is 0.8 to 1.2:1, preferably 0.9 to 1.1:1.
[0023] Furthermore, in step S6, the concentration of the KCl solution is 0.5-2 mol / L, and the desorption temperature is 40-70°C, preferably 50-60°C.
[0024] The beneficial effects of the present invention are:
[0025] The present invention can release rubidium elements in a short time under a relatively low temperature environment, and selectively extracts rubidium elements from rubidium-enriched liquid through composite materials, further improving the directional selective resource utilization effect of rubidium. In addition, the present invention optimizes the rubidium extraction process by accurately controlling particle size distribution, additive ratio, roasting conditions, leaching parameters, stirring speed and temperature, and desorption conditions, thereby improving the rubidium extraction efficiency and selectivity. This method not only reduces energy consumption and environmental pollution, but also reduces the cost of rubidium extraction and improves economic benefits. By using MOFs materials, the present invention also achieves efficient adsorption and desorption of rubidium, further improving the controllability and flexibility of the rubidium extraction process. In addition, the method of the present invention also has the advantages of simple operation, low equipment requirements, and easy industrial scale-up, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a process flow chart of the present invention.
[0027] Figure 2 These are SEM and EDS images of the original lithium ore tailings sample and the roasted sample of Example 2 of the present invention, wherein (a) is the original lithium ore tailings, (b) is the roasted sample, and (c) is the leached slag. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereby.
[0029] In the following examples, unless otherwise specified, the raw materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0030] The preparation methods of the four rubidium-extracting composite materials are as follows:
[0031] (1) KCoFC@UIO-66: prepared from potassium ferrocyanide trihydrate, cobalt nitrate hexahydrate, p-phenylene carboxylic acid, DMF, acetic acid and zirconium oxychloride octahydrate. Specifically, 10 mL of 0.5 mol / L potassium ferrocyanide trihydrate was added to 24 mL of 0.3 mol / L cobalt nitrate hexahydrate at room temperature and stirred for 1 h. The mixture was washed with deionized water and centrifuged three times to remove excess cobalt nitrate. The centrifuged product was dried at 115°C for 24 h. The dried particles were ground through a 100 mesh sieve to obtain potassium cobalt hexacyanoferrate. 15 mol of p-phenylcarboxylic acid was added to a beaker containing 120 mol of potassium cobalt hexacyanoferrate, 30 mL of N,N'-dimethylformamide (DMF) and 18 mL of acetic acid. After being fully stirred at room temperature for 30 min, 5 mol of chromium oxychloride octahydrate was added to the beaker of the mixture and stirred for 2 h. The mixture was placed in a 100 mL autoclave and heated at 150 ° C for 24 h. The mixture was then placed in a 50 mL centrifuge tube, centrifuged at 8000 rpm for 10 min, and then washed with anhydrous ethanol and DMF 3 times each to wash away excess ions and ensure that there were no impurity ions on the surface of the material. The bottom dark green solid phase was separated to obtain the final product, and vacuum dried at 65 ° C for 8 h until the quality was stable to obtain the final metal organic framework material KCoFC@UIO-66.
[0032] (2) Potassium cobalt hexacyanoferrate material (KCoFC): prepared from potassium ferrocyanide trihydrate and cobalt nitrate hexahydrate. Specifically, 10 mL of 0.5 mol / L potassium ferrocyanide trihydrate was added to 24 mL of 0.3 mol / L cobalt nitrate hexahydrate at room temperature and stirred for 1 h. The mixture was washed with deionized water and centrifuged three times to remove excess cobalt nitrate. The product after centrifugation was dried at 115°C for 24 hours. The dried particles were ground through a 100 mesh sieve to obtain potassium cobalt hexacyanoferrate (KCoFC).
[0033] (3) UIO-66 material: prepared from phenyl carboxylic acid, DMF, acetic acid and zirconium oxychloride octahydrate as raw materials, specifically, 0.5000 g of zirconium oxychloride octahydrate was added to 15 mL of DMF and ultrasonicated for 15 min, then 0.2575 g of terephthalic acid and 9.3 mL of acetic acid were added and ultrasonicated for 30 min, and the mixture was placed in a 100 mL autoclave and heated at 150° C. for 24 h. The mixture was then placed in a 50 mL centrifuge tube, centrifuged at 8000 rpm for 10 min, and then washed with anhydrous ethanol and DMF for 3 times each to wash away excess ions and ensure that there were no impurity ions on the surface of the material, and vacuum dried at 65° C. for 24 h until the quality was stable to obtain the UIO-66 material.
[0034] (4) Ammonium phosphotungstate-sodium alginate material: prepared with calcium chloride, sodium alginate and ammonium phosphotungstate as raw materials, specifically, first prepare 0.5 mol / L calcium chloride solution and 1.5% sodium alginate sol, according to the material ratio m(NaALG):m(AWP)=1:2, gradually add ammonium phosphotungstate to the sodium alginate sol, and ensure that the two are fully mixed to obtain a mixed glue. Use a medical syringe to absorb the above mixed glue, and slowly add it drop by drop to the previously prepared 0.5 mol / L calcium chloride solution. After the dropwise addition is completed, the mixture is allowed to stand at room temperature for 24 hours. After the sedimentation is completed, the composite adsorbent is separated by vacuum filtration and washed with deionized water several times to ensure that the calcium chloride remaining on the surface is removed. After filtration, it is placed in an electric hot air drying oven preheated to 105°C and dried to constant weight. Finally, the ammonium phosphotungstate-sodium alginate material is obtained.
[0035] Example 1
[0036] A method for selectively extracting rubidium from lithium ore tailings in a short process, the process flow is as follows Figure 1 As shown, the following steps are included:
[0037] S1. Take 10g of lithium ore waste rock tailings, dry and crush them to obtain lithium ore waste slag powder with a particle size range of 0 to 100 μm and more than 98%. The main chemical component content (mass percentage) of the lithium ore tailings used in this embodiment is shown in Table 1.
[0038] Table 1 Main chemical components of lithium ore tailings
[0039] Oxide <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[K2O]]> CaO <![CDATA[Fe2O3]]> MgO <![CDATA[Na2O]]> <![CDATA[Rb2O]]> other Proportion / % 62.7 20.7 5.06 4.25 3.61 1.59 1.26 0.227 0.603
[0040] S2. Take 5g of calcium chloride, 3g of oxalic acid and 10g of original lithium ore tailings sample, mix them thoroughly and evenly to prepare a mixed sample.
[0041] S3. The mixed sample is heated to 700° C. and calcined for 2 hours to obtain a calcined material.
[0042] S4. The roasted material is in powder form and does not need further grinding. It is directly leached completely. It is water-leached at a leaching temperature of 25°C and a leaching time of 30 minutes. The liquid-solid mass ratio of water to the roasted material is 4:1. The leachate is treated by solid-liquid separation to obtain rubidium-enriched solution and leaching residue.
[0043] S5. The prepared rubidium-extracting composite material KCoFC@UIO-66 and the rubidium-enriched solution were mixed and stirred at a mass ratio of 1:1 at 25°C and a stirring speed of 250 r / min for 2 hours to form a mixed solution;
[0044] S6. Perform solid-liquid separation on the mixed liquid to separate the rubidium-enriched material.
[0045] S7. Place the rubidium-enriched material in a 1 mol / L KCl solution, heat it to 50°C for desorption treatment for 30 minutes, and obtain rubidium-enriched pure liquid and regenerated rubidium-extracted composite material through solid-liquid separation.
[0046] The experimental results show that under the above conditions, after the roasted lithium ore tailings are completely leached, the rubidium concentration in the rubidium-enriched solution reaches 142.91 mg / L, and the extraction rate of the rubidium element reaches 89.94%.
[0047] The concentration of rubidium ions and the content of main interfering metal elements in the rubidium enriched solution were accurately measured by atomic absorption spectrophotometer (AAS) and inductively coupled plasma mass spectrometry (ICP-MS). The process parameters and leaching rate of the raw materials are shown in Table 2, and the basic data of the leaching solution are shown in Table 3.
[0048] Examples 2 to 22 show methods for selectively extracting rubidium from lithium tailings in a short process and in a short time with different process parameters. Compared with Example 1, the difference is that the process parameters of the chlorination roasting process of the original lithium tailings are changed, and the remaining steps are consistent with Example 1 and are not repeated here. The selective adsorption of the composite material will be discussed in detail in Examples 23 to 26.
[0049] The parameters corresponding to Examples 1 to 22 and the leaching rates obtained by testing and calculation are shown in Table 2.
[0050] Table 2 Process parameters and leaching rates of Examples 1 to 22
[0051]
[0052] As shown in Table 2, in the process of extracting rubidium by chlorination roasting, the roasting time and roasting temperature, leaching time, leaching temperature, solid-liquid ratio and other process parameters during roasting all have a significant effect on the leaching rate of rubidium. The present invention can achieve efficient extraction of rubidium in a short time at a lower temperature by finely regulating and optimizing these process parameters, and the maximum leaching rate can reach 91.80%, effectively overcoming the technical shortcomings of the traditional leaching method, such as long leaching time, high energy consumption and low leaching rate.
[0053] Examples 23 to 26 further provide a method for selectively extracting rubidium from lithium tailings in a short process and in a short time by changing different adsorbent materials. Compared with Example 1, these examples use 4 different adsorbents for selective rubidium adsorption in the treatment of the leachate after chlorination roasting of the original lithium tailings. The remaining steps are the same as those in Example 1 and are not repeated here. The residual amounts of different metals in the adsorbents and leachates corresponding to each example are shown in Table 3. In addition, the regeneration experimental results of the KCoFC@UIO-66 adsorbent material in Example 1 are recorded in detail in Table 4.
[0054] Table 3 Leachate data under optimal conditions and data after adsorption by different materials
[0055] Example Rb / ppm Na / ppm Mg / ppb Ca / ppm K / ppm Zn / ppb Original leachate 142.91 175.8 228.7 540.5 903.9 530.7 23 KCoFC@UIO-66 1.012 172.3 223.4 540.3 960.1 528.3 24 KCoFC 98.71 138.9 219.9 515.8 934.9 469.1 25 UIO-66 130.836 78.19 212.6 539.8 909.8 317.8 26 Ammonium phosphotungstate-sodium alginate 127.899 73.47 224.6 538.3 911.8 335.3
[0056] Table 4 Repeated regeneration of KCoFC@UIO-66 adsorption material
[0057] Rb / ppm Rb adsorption amount / (mg / g) Repeat 1 1.012 141.898 Repeat 2 2.197 140.713 Repeat 3 5.693 137.217 Repeat 4 8.1622 134.747 Repeat 5 16.909 126.001
[0058] As can be seen from Tables 3 and 4, the composite adsorption material prepared by the present invention exhibits a significant selective adsorption capacity for rubidium in the leachate. After 5 adsorption-desorption cycles, the selective adsorption capacity of the composite material for rubidium is still maintained at 88.8% of the initial adsorption amount, which proves that it can quickly, efficiently and selectively adsorb rubidium from the leachate. The method of the present invention avoids the common problems of long time consumption, complicated operation and low efficiency of repeated regeneration in traditional rubidium adsorption technology.
[0059] In summary, the method for selectively extracting rubidium from lithium ore tailings provided by the present invention adopts an integrated process of chlorination roasting-short-time low-temperature water leaching-composite material selectively adsorbing rubidium. First, the ground lithium ore tailings are uniformly mixed with calcium chloride and oxalic acid to form a roasting material, and then roasted and kept warm at a predetermined temperature. After the reaction is completed, it is naturally cooled to room temperature to directly obtain the leached material; then, the leached material is mixed with water in a predetermined proportion, stirred and leached at a set temperature, and the rubidium-containing enriched solution (leached solution) and leached residue are obtained by filtration; finally, at room temperature, the composite adsorbent material is added to the rubidium enriched solution in a fixed proportion to achieve selective adsorption of rubidium. Through this process, the present invention can efficiently extract rubidium from lithium ore tailings. The whole process is simple to operate, low in energy consumption, short in time, high in leaching rate, and good in selectivity. It effectively overcomes the technical difficulties such as long time consumption, complex operation, and low efficiency of repeated regeneration in traditional rubidium adsorption technology, and has important practical application value.
Claims
1. A method for selectively extracting rubidium from lithium ore tailings in a short process, characterized in that: The following steps are involved: S1. Grinding the lithium ore tailings to obtain lithium ore tailings powder; S2. The lithium ore tailings powder obtained in step S1 and the composite additive are fully mixed to obtain a raw material raw material, wherein the composite additive is a mixture of calcium chloride and oxalic acid; S3. The raw material obtained in step S2 is roasted to obtain a roasted material; S4. The roasted material obtained in step S3 is cooled to room temperature and then immersed in water, and the leaching liquid is separated by solid-liquid separation to obtain a rubidium-enriched solution and a leaching residue; S5. Selecting a rubidium-extracted composite material and mixing it with the rubidium-enriched solution obtained in step S4 to obtain a mixed solution, wherein the rubidium-extracted composite material is a metal organic framework material MOFs; S6. The mixed liquid obtained in S5 is subjected to solid-liquid separation to separate rubidium-enriched material; the rubidium-enriched material is placed in a KCl solution, heated for desorption treatment, and after solid-liquid separation, a rubidium-enriched pure liquid and a regenerated rubidium-extracted composite material are obtained.
2. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S1, the lithium ore tailings powder has a particle size of 0 to 100 μm, and the proportion of the powder is more than 98%.
3. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S2, the mass ratio of calcium chloride to oxalic acid is 0.3-0.6:0.
5.
4. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S3, the calcination temperature is 600-900° C., and the calcination time is 0.5-3 h.
5. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S4, the water immersion temperature is 25 to 90° C., and the time is 2 to 120 minutes.
6. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S4, the roasting material is in powder form and does not need to be further ground. The mass ratio of the roasting material to water is 1:2-10.
7. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S5, the stirring speed is 100-950 r / min, the mixing temperature is 20-80° C., and the mixing time is 2 min-2 h.
8. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S5, the mass ratio of the rubidium-extracted composite material to the rubidium-enriched solution is 0.8-1.2:
1.
9. The method for selectively extracting rubidium from lithium ore tailings in a short process according to claim 1, characterized in that: In step S6, the concentration of the KCl solution is 0.5-2 mol / L, and the desorption temperature is 40-70°C.
Citation Information
Patent Citations
Roasting leaching treatment process for recovery of metal rubidium resources from copper sulfur tailings
CN103966460A
Method for efficiently separating rubidium and cesium through adsorption
CN112899480A
Preparation method of heteropolyacid salt functionalized MOF-based rubidium and cesium adsorbent
CN115703059A
Anhydrous process for the production of activated, defluorinated, sintered concentrates of lithium-containing aluminosilicates
DE102021132918A1
Cited By
Method for extracting lithium and rubidium in mica ore through low-temperature roasting of organic acid
CN121109777A
Energy-saving boiler and preparation method of rubidium selective absorption material
CN121429999A
Energy-saving boiler and preparation method of rubidium selective absorption material
CN121429999B